given f(x)=3^x-2 and g(x)=f(3x)+4, write the function rule for function g and describe the types of transformations that occur between function f and function g

Respuesta :

ustsr

The function rule for function g is g(x) = 3³ˣ ⁻ ² + 4

The types of transformations that occur between function f and function g are horizontal scaling by a scale factor of ¹/₃ and followed by vertical translation by 4 units upwards from graph f(x)

[tex]\texttt{ }[/tex]

Further explanation

Function is a relation which each member of the domain is mapped onto exactly one member of the codomain.

There are many types of functions in mathematics such as :

  • Linear Function → f(x) = ax + b
  • Quadratic Function → f(x) = ax² + bx + c
  • Trigonometric Function → f(x) = sin x or f(x) = cos x or f(x) = tan x
  • Logarithmic function → f(x) = ln x
  • Polynomial function → f(x) = axⁿ + bxⁿ⁻¹ + ...

[tex]\texttt{ }[/tex]

If function f : x → y , then inverse function f⁻¹ : y → x

Let us now tackle the problem!

[tex]\texttt{ }[/tex]

Given:

[tex]f(x) = 3^{x - 2}[/tex]

[tex]g(x) = f(3x) + 4[/tex]

Asked:

g(x) = ?

Solution:

If [tex]f(x) = 3^{x - 2}[/tex] , then:

[tex]h(x) = f(3x)[/tex] → Horizontal Scaling by a scale factor of ¹/₃ (Scaling in the x - direction) from graph f(x)

[tex]h(x) = 3^{3x - 2}[/tex]

[tex]\texttt{ }[/tex]

[tex]g(x) = h(x) + 4[/tex] → Vertical Translation by 4 units upwards (Translation in the y-direction) from graph h(x)

[tex]g(x) = 3^{3x - 2} + 4[/tex]

[tex]\texttt{ }[/tex]

Conclusion:

The function rule for function g is [tex]\boxed{ g(x) = 3^{3x - 2} + 4 }[/tex]

The types of transformations that occur between function f and function g are horizontal scaling by a scale factor of ¹/₃ and followed by vertical translation by 4 units upwards from graph f(x)

[tex]\texttt{ }[/tex]

Learn more

  • Inverse of Function : https://brainly.com/question/9289171
  • Rate of Change : https://brainly.com/question/11919986
  • Graph of Function : https://brainly.com/question/7829758

Answer details

Grade: High School

Subject: Mathematics

Chapter: Function

Keywords: Function , Trigonometric , Linear , Quadratic, Transformations

#LearnWithBrainly

Ver imagen ustsr

Answer:

g(x) = 3^(3x-2)+ 4

transformations: horizontal compression and vertical translation

Step-by-step explanation:

Given

f(x)=3^(x-2)

To get f(3x) replace x by 3x:

f(3x) = 3^[(3x)-2] = 3^(3x-2)  

Add 4 to that result and get g(x):

g(x)=f(3x)+4 = 3^(3x-2)+ 4

g(x) has two parts, 'f(3x)' and '+ 4'

f(3x) -> horizontal compression by a factor of 3

+ 4 -> vertical translation up 4 units